Perancangan Sistem Informasi Penjualan Sepeda Motor Pada CV. Sun Berlian Berbasis Web - Sentosa Zega, Agus Mentro; Irmayani, Deci (Universitas Labuhanbatu, 2022)
Dealer CV. Sun Berlian Motor uses the Xai and Exoduz Program Program at the company in the process of calculating the stock of goods entering goods out, sales transactions, and transaction reports, so errors can still occur that are not too large starting from the stock of goods that are not the same but the company does not have an online system to sell motorcycle products online and to overcome these problems, we need a web-based system as one solution For that we need to optimize the use of computers for data processing by designing an information system that is applied to the PHP programming language and MySQL database in order to solve the problems that are exist by being able to answer the needs of the company. The purpose of this study was made to analyze the problems in the CV. Sun Berlian Motor which has not used the online system. It is expected that the system built will be truly able to overcome the problems that arise and be able to improve performance more effectively and efficiently in data management and transactions.